The Role of Purchase Intention in Mediating the Influence of Influencers and Online Customer Reviews on the Purchase Decisions of Electronic Products in E-Commerce (A Case Study in Denpasar City) - Ni Putu Sinria FRANZA; Ni Luh Putu INDIANI; Ni Made WAHYUNI (PT Keberlanjutan Strategis Indonesia, 2025)
The rapid growth of e-commerce has boosted the digital business climate but also intensified market competition. To stay competitive, businesses must go beyond technology by innovating their sales strategies, particularly in electronic products—the top-selling category in Indonesian e-commerce in 2023. This study analyzes how Influencers and Online Customer Reviews affect electronic product purchasing decisions in e-commerce, with Purchase Intention as a mediating variable. The population of this study consists of residents of Denpasar City who have made electronic product purchases through e-commerce platforms. The research method used is a survey, with data collected through questionnaires distributed to 160 respondents. Data analysis was conducted using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS). The results of the study show that Influencers have a positive and significant effect on both purchase intention and purchase decisions. Online Customer Reviews have a negative and significant effect on purchase decisions, but a positive and significant effect on purchase intention. The findings also indicate that purchase intention serves as a partial mediator in the relationship between Influencers and Online Customer Reviews on the purchase decisions of electronic products in e-commerce. These findings provide valuable insights for digital business players in designing more effective marketing strategies by utilizing Influencers and Online Customer Reviews to enhance purchase decisions for electronic products in e-commerce.